Literary Works as a Medium of Advocacy for Peace and Social Justice in Palestine: A Philosophical Value Study of Fadwa Tuqan's Poems - Liza, Fitri (International Tatho Academics, 2025)
This research identify two poems by Fadwa Tuqan,